Synthesis and biodegradability of polyaspartic acid: a critical review - Thombre, SM; Sarwade, BD (Journal of Macromolecular Science-Pure and Applied Chemistry, 2005)
Poly(aspartic acid) (PAA) being biodegradable is suitable for various industrial medical and agricultural applications to replace many non-biodegradable polymers in use. Poly(aspartic acid) can be synthesized by different methods with and without catalyst in different forms such as polysuccinimide, either hydrolyzed to acid or salt. The polymer of (aspartic acid) is present in different forms such as alpha, beta and L, D isomers. The conformational analysis of poly(aspartic acid) was done by various analytical methods. Different combinations of these two isomer present in different percentage can be detected by various methods such as Hoffman degradation, IR, and NMR spectroscopic analysis. From the standard test for biodegrad ability, it was shown that the polymer is fully biodegradable. In this review, synthesis and characterization of homo and copolymer derivatives of PAA, along with the application and biodegradability in comparison with the other polymer in use, is discussed briefly.
Keywords: Biodegradation; poly(aspartic acid); Polycondensation; polysuccinimide; synthesis; thermal